2019
DOI: 10.1021/acs.chemmater.8b04022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Alkali Metal Compound-Promoted Growth of Monolayer MoS2: Eutectic Intermediates

Abstract: Monolayer MoS 2 , processing flexibility and remarkable physical properties derived from its direct bandgap feature, has been endowed to be one of the potential materials for practical applications such as integrated circuits and logic devices. Recently, a facile CVD method using alkali metal compounds as promoters attracted a lot of attention. Here, we systematically investigated the mechanism of alkali metal compoundpromoted growth of monolayer MoS 2 by CVD and proposed a eutectic intermediate model. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 56 publications
1
91
1
Order By: Relevance
“…Now we will discuss the effect of NaCl in our gas-source CVD system. Previous studies have revealed that only cations play an important role in the alkali-metal assistance method 23 , so we have only considered the effects of Na. If Cl plays an important role in the mechanism, then CVD growth of TMDs from metal chloride (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now we will discuss the effect of NaCl in our gas-source CVD system. Previous studies have revealed that only cations play an important role in the alkali-metal assistance method 23 , so we have only considered the effects of Na. If Cl plays an important role in the mechanism, then CVD growth of TMDs from metal chloride (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These results shed light on one mechanism by which alkali-metal assistance functions during solid-source CVD. Prominent hypotheses are that the alkali metals increase the mass-flux by forming intermediates or that they promote the lateral growth of TMD once it has nucleated 21,23,25 . We think these two effects coexist in the solid-source CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason is that the introduction of NaOH enhances the lateral growth speed of MoS 2 . The eutectic intermediate containing alkali molybdate and molybdenum oxides has a low melting point, which could facilitate their mobility and lateral growth [21], weakening the epitaxial control from substrate and graphoepitaxial guide from surface steps. Thus, the triangular MoS 2 domains with large size and random arrangements were obtained when a large amount of NaOH was introduced.…”
Section: Growth Models Of Aligned Mos 2 Ribbonsmentioning
confidence: 99%
“…The microscopic mechanism of CVD is that the precursor of gas/vapor phase nucleates and then regenerates into films on the substrate [19]. A new molten salt-assisted CVD method for growing TMDCs has recently attracted attention [20][21][22][23][24][25]. The introduction of alkali metal promoter can effectively enhance the lateral growth of the film, making it a unique method for obtaining large-size single crystals.…”
Section: Introductionmentioning
confidence: 99%